Respuestas

2012-04-11T14:21:00+02:00

buenos dias.  a)f(x)=-3-----f(-1)=-1-3=-4

                                       f(0)=0-3=-3
                                       f(1)=1-3=-2
                    b)f(x)=2xalcuadrado+1---------2(-1)al cuadrado+1=2.1+1=3
                                                                2(0)al cuadrado+1=2.0+1=1
                                                                2(1)al cuadrado+1=2.1+1=3

                   c)f(x)=xalcubo-1-----------------f(-1)alcubo-1=-1-1=-2
                                                               f(0)al cubo-1=0-1=-1
                                                               f(1)al cubo-1=1-1=0
saludos.